Analysis of Gender and Interior Space Organization of Houses in Rural Settlements of North Cyprus - Kasım, Gülde (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Cypriots who are living in the rural areas of Cyprus and traditional dwellings are among the most important cultural values and heritage of the island. A country's past is the foundation of its future. The most important way to ensure the continuity of these important values is the protection of cultural heritage. The island of Cyprus has undergone great changes in terms of both its physical structure and socio-cultural structure from historical ages to the present. Looking at the history of the island, there are differences between the people who are living in the city and the people living in the village. Since the first ages, all people have started to shape their living spaces according to their needs. Urban dwellers generally preferred less functional apartment-type dwellings, while rural dwellers built traditional dwellings with a variety of functions due to their living standards. Unlike in the past, the situation in the countryside began to change. While there are great differences between gender roles in the past and today's gender roles, the user vision of Cyprus dwelling architecture has naturally changed. The main factors that shape the dwelling have been devalued by the changing socio cultural structure. The fact that the traces of the traditional texture in the countryside have begun to be erased poses a major problem for the Cypriot culture. In this study, to examine and reveal all these changes, traditional and contemporary dwellings selected from the rural areas of Mesarya and Beşparmak regions are discussed, the effect of gender roles on the dwelling, and the main factors that shape the dwelling are compared between the contemporary and traditional selected dwellings. The study is important in terms of understanding the factors behind the change process of dwelling, which is a cultural value, as well as gender roles that continue to change and the effects of these roles on dwellings. Keywords: Dwelling, Traditional and Contemporary Architecture, Culture, Gender Studies, Interior Design

ÖZ:Kıbrıs’ın kırsal kesimlerindeki Kıbrıslıların yaşam şekli ve geleneksel Kıbrıs konutları adanın en önemli kültürel değerlerinden ve miraslarındandır. Bir ülkenin geçmişi geleceğinin temelidir. Bu önemli değerlerin devamlılığını sağlamanın en önemli yolu ise kültürel mirasın korunmasıdır. Kıbrıs adası tarihi çağlardan günümüze kadar hem fiziki yapısı hem de sosyo-kültürel yapısı açısından büyük değişimler göstermiştir. Adanın tarihine bakıldığında, şehirde yaşayan ve köyde yaşayan insanlar arasında farklılıklar ortaya çıkmaktadır. İlk çağlardan itibaren tüm insanlar yaşam alanlarını ihtiyaçlarına göre şekillendirmeye başlamışlardır. Kentliler genellikle daha az işlevli apartman tipi evleri tercih ederken, kırsal kesimdekiler yaşam standartları nedeniyle, çeşitli işlevlere sahip olan geleneksel konutları inşa ediyorlardı. Geçmişten farklı olarak kırsalda durum değişmeye başladı. Geçmişteki toplumsal cinsiyet rolleri ile günümüzün toplumsal cinsiyet rolleri arasında da büyük farklar bulunurken, Kıbrıs konut mimarisinin kullanıcı vizyonu da doğal olarak değişmiştir. Konutu şekillendiren ana unsurlar, değişen sosyo-kültürel yapı tarafından değersizleştirilmiştir. Kırsal kesimde bulunan geleneksel dokunun izlerinin silinmeye başlamış olması, Kıbrıs kültürü için büyük bir sorun teşkil etmektedir. Bu çalışmada, tüm bu değişimleri incelemek ve ortaya çıkarmak adına Mesarya ve Beşparmak kırsal bölgelerinden seçilmiş geleneksel ve çağdaş konutlar ele alınarak, cinsiyet rollerinin konuta olan etkisi ve konutu şekillendiren ana faktörleri incelenerek seçilmiş olan çağdaş ve geleneksel konutlar arasında karşılaştırmalar yapılmıştır. Çalışma kültürel bir değer olan konutun değişim sürecinin arkasında bulunan faktörlerle birlikte, aynı zamanda değişim göstermeye devam eden toplumsal cinsiyet rollerini ve bu rollerin konuta olan etkilerini anlamak açısından önem göstermektedir. Anahtar Kelimeler: Konut, Geleneksel ve Günümüz Mimarisi, Kültür, Toplumsal Cinsiyet Çalışmaları, İç Mekan Tasarımı.
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2021. Supervisor: Prof. Dr. Kağan Günçe.
Keywords: Dwellings-Architecture; Architecture, Domestic-Cyprus, North; Dwelling; Traditional and Contemporary Architecture; Culture; Gender Studies; Interior Design